2010
DOI: 10.1128/aem.00315-10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Phenotypic Responses of Listeria monocytogenes Strains Possessing Different Growth Efficiencies under Acidic Conditions

Abstract: In an experiment delineating aciduric strains, food and clinical Listeria monocytogenes isolates tended to produce the most biomass whereas ovine and avian strains produced comparatively less biomass when exposed to high levels of sodium diacetate (SD) and potassium sorbate. Compared to reference strains that exhibited greater acid sensitivity, representative food isolates with comparatively good growth capacities in the presence of 21 mM SD at pH 5.0 accumulated reduced levels of acetate anion and K ؉ ion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 69 publications
(72 reference statements)
0
41
0
Order By: Relevance
“…Nevertheless, this potential cross-protective effect has not been assessed for other relevant food antimicrobial compounds. Further, the evidence of VirR regulon induction under acid stress prompted us to hypothesize that a potential cross-protective effect would be VirR mediated (43)(44)(45). Our results indicated that exposure to 2% PL increased subsequent NIS and EPL resistance of both the parent strain and the ⌬virR mutant.…”
Section: Figmentioning
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, this potential cross-protective effect has not been assessed for other relevant food antimicrobial compounds. Further, the evidence of VirR regulon induction under acid stress prompted us to hypothesize that a potential cross-protective effect would be VirR mediated (43)(44)(45). Our results indicated that exposure to 2% PL increased subsequent NIS and EPL resistance of both the parent strain and the ⌬virR mutant.…”
Section: Figmentioning
confidence: 67%
“…In contrast, there have been reports of a cross-protective phenomenon, where prior exposure to a stress may increase resistance against a subsequent stress (20, 42). Additionally, acid-induced transcriptome profiling in L. monocytogenes has suggested upregulation of stress-and virulence-related genes, including the VirR regulon, as part of acid stress adaptation (43)(44)(45). To test the hypothesis that prior exposure to organic acids induces crossprotection against the selected antimicrobials and is mediated by VirR, we exposed the L. monocytogenes parent strain and H7858 ⌬virR to BHI (no acid control), 2% PL, and 0.14% SD, followed by subsequent challenge with antimicrobial compounds.…”
Section: Preexposure To Organic Acids Induces Cross-protection In Anmentioning
confidence: 99%
“…Accumulation of intracellular ions is thought to have many growth-inhibiting effects, including reduction of the proton motive force, reduction of intracellular pH, interference with microbial metabolism, and anion toxicity (9,20,37). Bacteria respond to organic acid stress by transcriptional activation of the general stress (3,7) and oxidative stress (35) responses, membrane alterations (5) (possibly to reduce diffusion of organic acids or increase anion transport) (52), and metabolic changes (7,44,50). These organic acid responses appear to be distinct from the inorganic acid stress response caused by exposure to low pH from added HCl, which in L. monocytogenes includes activation of general stress responses, transcription of genes encoding proton pumps, and cell membrane modification (18,59).…”
mentioning
confidence: 99%
“…To date, acid stress response studies of bacteria have focused on acid-adapted exponential-phase (7,34) or stationary-phase (41) cells or on transcription differences during acid shock (exposures of less than 1 h) (3,5). As the end goal of bacteriostatic growth-inhibiting treatments in foods is to indefinitely extend the lag phase, our work focused specifically on the transcriptomic response to organic acid stress under conditions approximating adaptation (8 h into lag phase) during refrigerated storage (7°C, microaerophilic conditions) of a food product (pH 6.1, 4.65% water-phase [w.p.]…”
mentioning
confidence: 99%
“…In addition several other putative cold, osmotic, acid and alkaline stress protection genes and proteins are known from gene expression analysis, which now allows rationalized creation of deletion mutants for functional studies ( Bowman et al, 2010;Chan et al, 2007;Giotis et al, 2008;Giotis et al, 2010;Liu et al, 2002). One of the putative cold adaptation genes identified in this bacterium is the lmo0501 locus of L. monocytogenes EGDe, which codes for the putative transcription activator protein Lmo0501.…”
Section: Introductionmentioning
confidence: 99%